2014
DOI: 10.1002/ajmg.a.36634
|View full text |Cite
|
Sign up to set email alerts
|

QOL in caregivers of Japanese patients with Prader–Willi syndrome with reference to age and genotype

Abstract: This study aimed to measure quality of life (QOL) of the primary family caregivers for patients with Prader–Willi syndrome (PWS). Comparisons were made between caregivers' QOL in regard to their dependents' genotype and age group. The participants with PWS consisted of 22 children (aged from 6 to 12 years) and 23 adolescents (aged from 13 to 19 years), including 6 children and 7 adolescents with maternal uniparental disomy (mUPD) and 16 children and 16 adolescents with deletion (DEL). The QOL of the primary fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In the same line, a recent study showed that the total quality of life of caregivers of adolescents with a deletion was higher than in caregivers of adolescents with an mUPD [38]. The fact that psychiatric problems, like psychosis and autism spectrum disorder, are more common in children and adolescents with an mUPD than in those with a deletion could contribute to these findings [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, a recent study showed that the total quality of life of caregivers of adolescents with a deletion was higher than in caregivers of adolescents with an mUPD [38]. The fact that psychiatric problems, like psychosis and autism spectrum disorder, are more common in children and adolescents with an mUPD than in those with a deletion could contribute to these findings [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…There was only one study concerned with the QOL of caregivers, which might deteriorate during the late adolescence of patients with a mUPD genotype. However, the reason for this finding remains unclear ( Ihara et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there had previously been no appropriate condition-specific metrics for caregivers in Japan working with CP children. As an alternative it has been possible to use the Japanese version of the somewhat generalized World Health Organization QOL-BREF (WHOQOL-BREF)12 ) , which is aimed at assessing the QOL of primary family caregivers for patients with intractable and rare diseases13 ) . To the best knowledge of the authors, our study is the first attempt to translate the world-wide psychometric battery for testing the QOL of primary caregivers of CP children into Japanese.…”
Section: Discussionmentioning
confidence: 99%